2013
DOI: 10.1115/1.4025248
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Effect of Real Syngas Compositions on Ignition Delay Times and Laminar Flame Speeds at Gas Turbine Conditions

Abstract: Depending on the feedstock and the production method, the composition of syngas can include (in addition to H2 and CO) small hydrocarbons, diluents (CO2, water, and N2), and impurities (H2S, NH3, NO^, etc.). Despite this fact, most of the studies on syngas combustion do not include hydrocarbons or impurities and in some cases not even diluents in the fuel mixture composition. Hence, studies with realistic syngas composition are necessary to help in designing gas turbines. The aim of this work was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The production of ultra-clean transportation fuels from biomass (biomass-to-liquids or BTL) through the Fischer-Tropsch Synthesis (FTS) reaction has attracted increased attention in recent years; this is in addition to conventional routes from coal-to-liquids (CTL) and natural gas-to-liquids (GTL) [1][2][3][4]. The BTL process involves syngas production through the gasification of biomass materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of ultra-clean transportation fuels from biomass (biomass-to-liquids or BTL) through the Fischer-Tropsch Synthesis (FTS) reaction has attracted increased attention in recent years; this is in addition to conventional routes from coal-to-liquids (CTL) and natural gas-to-liquids (GTL) [1][2][3][4]. The BTL process involves syngas production through the gasification of biomass materials.…”
Section: Introductionmentioning
confidence: 99%
“…The BTL process involves syngas production through the gasification of biomass materials. Depending on the oxygen source for gasification, the H 2 /CO ratio derived from biomass varies in the range of 1.0 to 1.5 for air-blown gasification, and 1.5 -2.2 for gasification using pure O 2 [1,4]. However, the biomass-derived syngas generally contains a number of impurities such as sulfur compounds (e.g., H 2 S and COS), halide compounds (e.g., NaCl and KCl), nitrogen-containing chemicals (e.g., NH 3 , NO X and HCN), traces of metals (e.g., Hg and Pb), and other compounds (e.g., NaHCO 3 , KHCO 3 , HCl, HF, and HBr) in addition to ash and tars.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result at first may seem surprising, but it can be explained through recent, parallel studies by the authors. Mathieu et al [18] in their numerical study on the effect of hydrocarbons on the laminar flame speeds of H2-based syngas blends showed that the addition of hydrocarbons to the fuel tends to reduce significantly the flame speed; this effect is more pronounced for ethane than for methane, leading to SL,u values that are smaller for similar concentrations and conditions.…”
Section: Legendmentioning
confidence: 99%
“…Mathieu et al [12] measured the effects of variations in CH 4 , CO 2 , H 2 O, and NH 3 content on auto-ignition delay using a shock tube at ~98% Ar dilution, φ = 0.5, P = 2-32 atm, T = ~960-1860 K. The results indicated that the addition of up to 0.16% CO 2 , 0.22% H 2 O, or 0.02% NH 3 by total mixture volume had negligible effect at all conditions, while the addition of up to 0.08% CH 4 increased the auto-ignition delay time by up to an order of magnitude. Additionally, Mathieu et al [13] investigated the effects of several compounds on syngas auto-ignition delay time using numerical methods, considering the addition of up to 15% CH 4 , 1.7% C 2 H 6 , 5.3% C 2 H 4 , 0.7% C 2 H 2 , 21.8% H 2 O, and 15% CO 2 by total fuel volume for mixtures at air-dilution, φ = 0.5 and 1.0, P = 1-35 atm, T = 900 -1400K. The results of this work indicated that for all hydrocarbon (HC) species except C 2 H 2 an increase in the auto-ignition delay time by a factor of two or more is expected, with the most significant magnitude change for T > 1000 K. Gersen et al [14] measured the effects of variations in H 2 , CO, and CH 4 content on auto-ignition delay times using a rapid compression machine at approximately airdilution, φ = 0.5 and 1.0, P = ~20-80 bar, T = ~900-1100 K. The mole fraction of CH 4 in the fuel was varied from 0 to 1, for H 2 from 0 to 1, and for CH 4 from 0 to 0.5.…”
Section: Introductionmentioning
confidence: 99%